O efeito da estrutura da matriz na percepção de aves na paisagem - Giubbina, Marina Furlan [UNESP] (2015)
The increased demand for agricultural products results in intense habitat loss and fragmentation, causing spatial changes in landscapes and biodiversity loss. The intervening matrix, i.e. non-habitat environments surrounding habitat patches, can act as barrier in the movement of organisms between fragments, reducing the functional connectivity for many species. But the influence of matrix composition and its structure on fauna movement rarely has been quantified. Thus, this study aimed to evaluate the influence of the presence and structure of the matrix in the movement of two forest-dependent bird species: Thamnophilus caerulescens and Synallaxis frontalis. Twelve landscapes containing sugarcane and Eucalyptus matrices Using playback trials in the sinuosity the birds had the option of following the vocalizations from one point to another in the curve by two different routes, (1) a shorter one through the matrix and (2) another longer inside fragment's edge. The distances between the playbacks ranged from 30 to 130 meters. Control trials were done within the remaining, in which the vocalizations were first played at the forest edges. As the individuals answered the voalizations, the playback was reproduced 10 meters increasingly inside the remnant, observing the distances traveled by each species. Thus, through analysis of variance and GLMS, it observed that there is a greater preference by following the playback inside the forest edge than by the matrix. It was also found that there is a negative correlation between distance and probability to cross the matrix and the species followed playback at greater distances in control than in both routes. By comparing sugarcane and Eucalyptus it was found that the first was more permeable than the latter, demonstrating that the structure of the matrix interferes their permeability. The routes that individuals followed the playback differ between the matrices, and there was a greater expenditure of ...